Erector spinae plane block versus paravertebral block in breast surgeries - Raghuraman M. Sethuraman (BMC Anesthesiology, 2022)
Abstract This article (Correspondence) is in response to the recently published study by Elewa et al. in BMC Anesthesiology that compared the erector spinae plane block (ESPB) versus paravertebral block (PVB) regarding postoperative analgesic consumption following breast surgeries. I greatly appreciate the authors for publishing this study which is one among a very few studies available on this topic. I wish to present my reflections on this article as well as add a few more points on this topic.